Antecedents and outcome of donors' trust in waqf institutions : the case of Bangladesh - Hasan, Rashedul (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Waqf is a historical and charitable vehicle in Islam that has the potential to contribute toward the socio-economic development of a country. There has been a growing lack of trust in waqf institutions among donors from Muslim countries due to numerous problems such as misallocation of funds, the low level of information disclosure, weak governance mechanisms and the lack of accountability to stakeholders. Unlike Zakat, Waqf is a non-obligatory levy, which will be contributed by the donors based on the level of trust they have in the waqf institutions. Empirical investigation is undertaken in this study to establish elements that affect donor trust toward waqf institutions. This study is an attempt to develop and empirically test a model of the donors' trust toward waqf institutions. The antecedents and outcome model of the donor's trust is developed from the perspectives of Commitment-Trust, Islamic Accountability and Stewardship theory. The data for the study is gathered from 326 actual donors of publicly administered waqf institutions in Bangladesh using a self-administered questionnaire. The results from Structural Equation Modelling (SEM) provide validity of the developed model and statistical significance of seven hypotheses developed through critical review of literature. Board benevolence, board ability, board integrity, communication and accountability have a positive influence on the donors' trust while board opportunism affects trust negatively. Trust also has a significant positive impact on the donors' commitment toward waqf institutions. The survey results are compared and integrated with follow-up interviews with four waqf administrators in Bangladesh. The results of the study can guide the regulators in formulating policies that could increase the donors' trust in waqf institutions and ensure a sustainable future of these religious, charitable organisations.